APRENDIZAJE BASADO EN PROYECTO Y SU INFLUENCIA EN EL DESARROLLO DEL PENSAMIENTO CRÍTICO DE LOS ESTUDIANTES - PARRALES BASURTO SCARLET BELEN (2024)
In the city of Babahoyo, the "Juan E. Verdesoto" Basic Education School faces a challenge in the development of critical thinking of its seventh-grade students, who show tendencies towards memorization instead of understanding and questioning concepts, this limitation prevents the connection between various areas of knowledge and the effective application of critical thinking. To address this problem, the need to prioritize teaching that encourages critical thinking and the practical application of knowledge was raised. By considering Project-Based Learning (PBL), this methodology allows students to live enjoyable and direct experiences, thus promoting the development of skills that promote critical thinking. The research methodology was descriptive with a non-experimental design in which a qualitative approach was used and the analytical-synthetic method was used. An interview with the teacher, student surveys and observations were implemented to collect the data that allowed us to fulfill the objective of the research, which was to analyze the influence of Project Based Learning (PBL) on the development of critical thinking of 7th grade students. year during the period 2023-2024. The results showed how students' critical thinking can be strengthened through the implementation of Project Based Learning (PBL). It is concluded that this methodology can be a pedagogical tool to enhance critical thinking and the practical application of knowledge in the educational context of the "Juan E. Verdesoto" School of Basic Education.